2005
DOI: 10.1210/jc.2004-1375
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients after Long-Term Biochemical Cure of Cushing’s Disease

Abstract: To evaluate the long-term impact of cured Cushing's disease on subjective well-being, we assessed quality of life by validated health-related questionnaires in 58 patients cured from Cushing's disease by transsphenoidal surgery (n = 58), some of whom received additional radiotherapy (n = 11) and/or bilateral adrenalectomy (n = 3). The mean duration of remission was 13.4 +/- 6.7 yr (range of 2-25 yr). Patient data were compared with a control group of 98 healthy subjects with the same age and sex distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
194
5
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(220 citation statements)
references
References 39 publications
20
194
5
1
Order By: Relevance
“…However, only two studies have taken the possible role of GHD into account (6,7). In the present study, a significant improvement in QoL was observed after 3 years of GH treatment.…”
Section: Analysis Bsupporting
confidence: 45%
See 1 more Smart Citation
“…However, only two studies have taken the possible role of GHD into account (6,7). In the present study, a significant improvement in QoL was observed after 3 years of GH treatment.…”
Section: Analysis Bsupporting
confidence: 45%
“…QoL has previously been shown to be impaired in patients with controlled Cushing's disease (6,7,17,18). However, only two studies have taken the possible role of GHD into account (6,7).…”
Section: Analysis Bmentioning
confidence: 99%
“…These clinical improvements are very important to the patien- t's quality of life, once it represents the return to normal activities. Some studies suggest that even cured patients might continue to have a poor quality of life (43)(44)(45)(46). Possible explanations for this observation are the definitive systemic damage caused by CD or are associated to the poor biochemical criteria adopted.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…4,17 However, many patients do not achieve a premorbid level of functioning and experience persistent impairment of QoL and cognitive function. 24,35 Brain morphologic changes, including cerebral atrophy and decreased hippocampal volume associated with cognitive decrement and depressive symptoms, have been reported in adults with active CS and are partially reversible after cure. 5,36,37 These data highlight the need for prospective research to investigate the long-term psychological and cognitive morbidities.…”
Section: Discussionmentioning
confidence: 99%